2019
DOI: 10.1016/j.jfda.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Rubiscolin-6 activates opioid receptors to enhance glucose uptake in skeletal muscle

Abstract: Rubiscolin-6 is an opioid peptide derived from plant ribulose bisphosphate carboxylase/oxygenase (Rubisco). It has been demonstrated that opioid receptors could control glucose homeostasis in skeletal muscle independent of insulin action. Therefore, Rubiscolin-6 may be involved in the control of glucose metabolism. In the present study, we investigated the effect of rubiscolin-6 on glucose uptake in skeletal muscle. Rubiscolin-6-induced glucose uptake was measured using the fluorescent indicator 2-[N-(7-nitrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…3E ), CLH supplementation sustained the insulin signal sensitivity in skeletal muscle and peri-renal fat tissues against the long-term HFD feeding because of the downstream GLUT4 response to upstream insulin signal in CLH cotreated mice compared to that of HFD group. Kairupan et al reported that expressions of GLUT4 were modulated by upstream AMPK signal in skeletal muscle, which was consistent to our results [ 36 ]. Graham et al proposed that the amount of GLUT4 in white adipose tissues represented a good systemic insulin sensitivity marker [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…3E ), CLH supplementation sustained the insulin signal sensitivity in skeletal muscle and peri-renal fat tissues against the long-term HFD feeding because of the downstream GLUT4 response to upstream insulin signal in CLH cotreated mice compared to that of HFD group. Kairupan et al reported that expressions of GLUT4 were modulated by upstream AMPK signal in skeletal muscle, which was consistent to our results [ 36 ]. Graham et al proposed that the amount of GLUT4 in white adipose tissues represented a good systemic insulin sensitivity marker [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although its function is not clear, rubiscloin-6 has been shown to have a higher receptor affinity and is about twice as potent in analgesia as rubiscolin-5 [ 21 ], as was observed in our study. Rubiscolin-6 has also been reported to have broad beneficial effects related to the central nervous system, other than analgesia [ 22 , 23 , 24 , 25 , 26 ]. As an example, for the development of DOR selective agonists, considering such effects, NC-2800 is under Phase 1 clinical study to determine the indication of major depressive disorder ( accessed on 30 September 2021).…”
Section: Discussionmentioning
confidence: 99%
“…administration in mice [ 21 ], which never occurs for endogenous opioid peptides. Moreover, rubiscolins are promising in terms of their unique effects other than analgesia, such as memory consolidation [ 22 ], anxiolytic effect [ 23 ], stimulation of food intake [ 24 ], enhancement of glucose uptake in skeletal muscle [ 25 ], and antidepressant-like effect [ 26 ]. Although the potency and actions of rubiscolins as G-protein-biased molecules were partially confirmed in a previous study using DOR [ 27 ], their in vitro profiles have not been sufficiently revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results ( Table 1 and Figure 1 ), our CLHs demonstrated similar hypoglycemic effects in STZ injected mice as ACTOS , which might be due to improving the insulin sensitivity in STZ injected hyperglycemic mice. Besides, GLUT 4 is a key determinant of glucose homeostasis, which permits the facilitated diffusion of serum glucose into muscle, adipose, liver and brain cells ( Kairupan et al, 2019 ), and BCAAs can stimulate the GLUT 4 activity and insulin sensitivity, thus decreasing blood glucose levels ( Nishitani et al, 2005 ), and there is the amount of BCAAs in our CLHs ( Supplementary Table 1 ). Isoleucine supplementation could potentially increase muscle growth and intestinal development by enhancing local glucose uptake in animals and human beings via upregulations of the intestinal and muscular GLUT 1 and GLUT 4 expressions ( Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%